Mapping of the evidence from systematic reviews of the Cochrane Collaboration for decision-making within physiotherap - Versiani, Ane Helena Valle; Martimbianco, Ana Cabrera; Peccin, Maria Stella (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Evidence-based clinical practice emerged with the aim of guiding clinical issues in order to reduce the degree of uncertainty in decision-making. The Cochrane Collaboration has been developing systematic reviews on randomized controlled trials as high-quality intervention study subjects. Today, physiotherapy methods are widely required in treatments within many fields of healthcare. Therefore, it is extremely important to map out the situation regarding scientific evidence within physiotherapy. The aim of this study was to identify systematic reviews on physiotherapeutic interventions and investigate the scientific evidence and recommendations regarding whether further studies would be needed. TYPE OF STUDY AND SETTING: Cross-sectional study conducted within the postgraduate program on Internal Medicine and Therapeutics and at the Brazilian Cochrane Center. METHODS: Systematic reviews presenting physiotherapeutic interventions as the main investigation, in the Cochrane Reviews Group, edition 2/2009, were identified and classified. RESULTS: Out of the 3,826 reviews, 207 (5.41%) that fulfilled the inclusion criteria were selected. Only 0.5% of the reviews concluded that the intervention presented a positive effect and that further studies were not recommended; 45.9% found that there seemed to be a positive effect but recommended further research; and 46.9% found that the evidence was insufficient for clinical practice and suggested that further research should be conducted. CONCLUSION: Only one systematic review (“Pulmonary rehabilitation for chronic obstructive pulmonary disease”) indicated that the intervention tested could be used with certainty that it would be effective. Most of the systematic reviews recommended further studies with greater rigor of methodological quality.